Analisis Semiotika terhadap Tradisi Duduk Bersama: Mengungkap Simbol Sosial dalam Tradisi Indonesia - Nangoy, Oktavianus Marti; Kresna, Aryaning Arya (YASIN, 2025)
The objectives to be achieved in this study emphasize the semiotic analysis of the tradition of sitting together in revealing the social symbols of Indonesian tradition. The method used in this study is qualitative with a hermeneutic approach where researchers use meaning and text or social phenomena contained in the history of the culture of sitting together. The results of this study indicate that interaction with technological advances is still able to maintain the existence of the culture of sitting together where this mechanism emphasizes solidarity and a sense of togetherness. Physical and face-to-face relationships cannot be replaced by socialization that is established in the digital realm considering that direct interaction with each other will create space to maintain social values ​​and respect each other. In addition, in the future this tradition is able to provide potential on the basis of pluralism and diversity where it is based on social polarization. Thus the tradition of sitting together is still a relevant habit in social life and builds a big impact in the future.